Umwandlung von Lichtenergie in chemische Energie - Gion Calzaferri (CHIMIA)
The conversion of light into chemical energy as well as the conversion of chemical energy into light leads to exciting speculations and experiments. Reversible photoredox reactions appear to be the most promising chemical system for converting solar energy into chemical or electrochemical energy. Finding selective electrode material in photogalvanic cells is one of the problems to be solved. By now we have found such selective electrode material for (Fe3+)aq/(Fe2+)aq in the thionine/iron system as well as in the iodine/iron system. – Our main attention should now be focused on reversible two or more photon processes at low light intensities, because cleveage of water in the visible region cannot be done with one photon.